Trophic roles of scavenger beetles in relation to decomposition stages and seasons - Zanetti, Noelia Inés (2015)
Carcasses represent a trophic and reproductive resource or shelter for arthropods, which are a representative component of the decomposition process. Four experiments, one per season, were conductedin a semi-rural area of Bahía Blanca, Argentina, to study the trophic roles of cadaveric beetles, evaluating the abundance, composition and dominance during all decomposition stages and seasons. Speciesof necrophagous, necrophilous and omnivorous habits were found. Abundance, composition and dominance of beetles in relation to their trophic roles changed according to seasons and decomposition stages. Guilds and patterns of succession were established in relation to those periods. Trophic roles could be anindicator of beetle associations with decomposition stages and seasons.